Analysis of determining optimal portfolio in BPKH’s portfolios using Tangency Portfolio model - Agam Maulana Ardi; Darwanto Darwanto (Faculty of Economics, Universitas Islam Indonesia, 2023)
Purpose – This study aims to analyze the actual portfolio of BPKH from the hajj fund investment and examine the optimization investment portfolio for BPKH based on PP No.5 Tahun 2018.Methodology – The data used in this study was quarterly in the form of price and coupon for Sukuk instruments and the equivalent of yield rate for Sharia deposits. This study uses the Markowitz Diversification method with the Tangency Portfolio model as a model to determine optimal portfolio. Findings – The result of this study showed that BPKH’s actual portfolios in 2018 and 2019 can’t be determined as efficient portfolios and the optimal portfolio. Meanwhile, BPKH’s actual portfolios in 2020 and 2021 are included as efficient portfolios but not optimal portfolio. The result of an optimal portfolio in this study has a composition as follows: 30% of Sharia deposits, 5,60% of SBSN, and 64,40% of SDHI.Implication – The finding of an optimal portfolio can recommend BPKH to allocate most of the hajj fund in SDHI than SBSN because the SBSN has high risk and still to allocate in Sharia deposits as worth maximum based on regulation in PP No.5 Tahun 2018. BPKH needs to diversify hajj fund investment wider such as Lembaga Tabung Haji (LTH) has done in Malaysia.Originality – This study contributes to evaluate of whether BPKH’s actual portfolios in the first third years since BPKH operation and after the first third years of BPKH operation are efficient and optimal or not. Furthermore, this study provides a combination of instruments in the scenario optimal portfolio.